Minat dan Keputusan Mahasiswa Menggunakan QRIS : Tinjauan dari Perspektif Persepsi - Vania Vashti; Amelia Setiawan; Hamfri Djajadikerta (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of perceived ease of use, perceived security, and ease of finding QRIS-enabled outlets on the intention to use and the actual usage decision of QRIS as a transaction tool among active university students. This research employs a quantitative approach, collecting data through an online questionnaire distributed via Google Forms to 118 active students who have used QRIS. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the SmartPLS 4 application. The results indicate that the three independent variables have a positive and significant effect on the intention to use QRIS. Furthermore, the intention to use was also found to have a significant impact on the usage decision. These findings suggest that positive perceptions regarding technological ease, transaction security, and outlet accessibility play an important role in driving QRIS adoption among students. This study is expected to serve as a reference for formulating strategies to increase the use of digital payment systems in higher education environments.